Interference of Noxious Shrubs on Grazing Behavior by Bovines - MARCHI,S.R. (2019)
ABSTRACT: The grazing behavior practice by bovines can be positive or negatively influenced by the pasture structure where the animal is inserted. Several factors determine the pasture structure and the presence of weeds is considered one of the most important. This study aimed to assess the effect of species with and without stiff structures over the grazing behavior of bovines in pasture areas. The experimental design was a split block design with four replications, in which treatments were arranged in a 4 x 3 factorial design: four weed species (Zanthoxylum rhoifolium, Cnidoscolus urens, Dasyphyllum brasiliensis, and Luehea divaricata) associated with three proximity strips of weeds: 0-50, 50-100, and 100-150 cm in relation to the main stem of the studied weed. Forage intake by animals was measured by determining the real forage offers at 0, 3, 6, 9, and 15 days after the beginning of animal grazing (DAP). The presence of noxious shrubs influenced bovine grazing behavior. The influence on the intake is most evident in the presence of plants that promote animal discomfort. The species Z. rhoifolium, C. urens, and D. brasiliensis were the weeds with the greatest influence on feed access among the species that have stiff structures. The negative influence on grazing behavior is higher in the proximity strip closest to the plant, i.e. 0-50 cm from the main stem of the weed.